Table 1_Taking stock of psychosocial rehabilitation in children and adolescents: a systematic review with meta-analysis.docx - Liesa J. Weiler-Wichtl (22686938) (2025)
Objective Psychosocial rehabilitation for children and adolescents with physical illnesses remains underdeveloped and poorly defined. This systematic review and meta-analysis aimed to consolidate current research findings. Design We searched Medline, PsycINFO, Scopus, Web of Science, and a guideline registry, with the last search conducted on August 30, 2023. Subjects/patients Children and adolescents with physical indications. Methods Eligible studies reported time-limited rehabilitation programs conducted in dedicated facilities, excluding those focused on psychiatric conditions. Results In all, 18 studies were eligible (N = 2,933). Meta-analysis (k = 4, i = 11, N = 418) revealed a moderate, statistically significant effect size (d = 0.48) for psychosocial rehabilitation in improving quality of life, mood, and anxiety. However, research in this field proved scattered and inconsistent, as few controlled trials were available, and there was little agreement regarding research designs, procedures, and outcome measures. Conclusion Psychosocial rehabilitation shows promising effects, but stronger evidence is needed to validate its efficacy. The lack of standardized definitions and procedures hinders progress. Future research should focus on randomized controlled trials and larger samples to optimize rehabilitation practices and improve outcomes for young patients with somatic conditions, resulting in evidence-based guidelines. Systematic Review Registration https://doi.org/10.17605/OSF.IO/AM2Z9